Pengaruh Insentif Pajak Terhadap Kinerja Keuangan UMK Di Kota Makassar - Fitri Ramadhani; Ratna Sari; Muhammad Arif (Paradoks : Jurnal Ilmu Ekonomi, 2021)
Taxes are the largest source of revenue in Indonesia. Sources of tax revenue come from many sectors, one of which is UMKM. Micro, Small and Medium Enterprises (UMKM) are businesses or businesses carried out by individuals, groups, small business entities, and households. Indonesia as a developing country makes UMKM the main foundation of the community's economic sector. This study aims to determine whether there is a positive effect of 0.5% tax incentives on the financial performance of UMK in Makassar City. This study uses a quantitative research approach. The sample in this study were 30 UMK in the city of Makassar. Data collection techniques using observation, interviews and documentation. The data analysis technique used to answer the hypothesis is simple linear regression. The results of this study indicate that the 0.5% tax incentive variable has a significant level of 0.000, which is smaller than 0.05. A decent t value of +8,395 indicates that the effect given is positive on the dependent variable. So it can be said that the 0.5% tax incentive has a positive and significant effect on the financial performance of UMK in the city of Makassar.